Crystallite distribution analysis based on hydrogen content in thin-film nanocrystalline silicon solar cells by atom probe tomography. (16th December 2020) - Shimizu, Yasuo; Sai, Hitoshi; Matsui, Takuya; Taki, Kenji; Hashiguchi, Taiki; Katayama, Hirotaka; Matsumoto, Mitsuhiro; Terakawa, Akira; Inoue, Koji; Nagai, Yasuyoshi
Abstract: The three-dimensional (3D) distribution of nanosized silicon (Si) crystallites within a hydrogenated nanocrystalline Si (nc-Si:H) material is examined by laser-assisted atom probe tomography (APT). The amorphous and crystalline phases in nc-Si:H are distinguished by obtaining the 3D density distribution of H atoms, because the former contains a high H density. The H content in the amorphous phase is estimated to be approximately 15 at% by APT, which is consistent with that obtained by infrared spectroscopy. Thus, the 3D analysis of H distribution via APT is a powerful method to visualize the real shape of nanosized crystallites within nc-Si:H materials.